2022
DOI: 10.1177/00049441221130551
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ perspectives about teaching and supporting students with learning difficulties in reading

Abstract: We explored the perspectives of school-based educators located in Victoria, Australia, regarding their support of students who have reading difficulties. An anonymous survey was completed by 523 participants, including educators, educational leaders and Student Support Services staff. Results revealed multiple areas of concern related to their capacity to work on reading intervention with these students. Although participants reported that students with reading difficulties were present in most classes, confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Thirdly, the inclusion of a Response to Intervention (RTI; Fuchs & Fuchs, 2006) criterion has had considerable consequences in terms of equity and the accessibility of diagnoses (Shaywitz & Shaywitz, 2020); in cases where students are not provided with adequate instruction (at Tier 1) and targeted intervention (at Tiers 2 and 3) at school, a formal diagnosis is only possible if intervention is accessed privately, at great cost to families. In Australia, research conducted by Serry et al (2022) on the attitudes and beliefs of school-based educators working with children with learning difficulties in reading (LD) found that 36% of participants did not feel confident teaching a student with LD, 41% did not have the time to teach students with LD and more than half of all participants reported that they did not have the resources to teach students with LD. Regarding Tier 2 and 3 support, Quick (2020) found that only 52% of Australian schools offer any kind of literacy intervention, and only 20% offer intervention programs that prioritise phonics and phonological awareness.…”
Section: Assessment Practices Used To Identify Gifted-dyslexic (G-d) ...mentioning
confidence: 99%
“…Thirdly, the inclusion of a Response to Intervention (RTI; Fuchs & Fuchs, 2006) criterion has had considerable consequences in terms of equity and the accessibility of diagnoses (Shaywitz & Shaywitz, 2020); in cases where students are not provided with adequate instruction (at Tier 1) and targeted intervention (at Tiers 2 and 3) at school, a formal diagnosis is only possible if intervention is accessed privately, at great cost to families. In Australia, research conducted by Serry et al (2022) on the attitudes and beliefs of school-based educators working with children with learning difficulties in reading (LD) found that 36% of participants did not feel confident teaching a student with LD, 41% did not have the time to teach students with LD and more than half of all participants reported that they did not have the resources to teach students with LD. Regarding Tier 2 and 3 support, Quick (2020) found that only 52% of Australian schools offer any kind of literacy intervention, and only 20% offer intervention programs that prioritise phonics and phonological awareness.…”
Section: Assessment Practices Used To Identify Gifted-dyslexic (G-d) ...mentioning
confidence: 99%
“…This difficulty causes students to find it difficult to express opinions and behavior in the form of words or sentences during lectures. Serry et al (2022) said difficulty reading and writing can be caused by internal factors such as nervous disorders or external factors from a disturbing environment. Students and lecturers must be able to identify the causes and continue to support students who experience reading difficulties by continuing to invite them to contribute during learning.…”
Section: Language (Language Difficult)mentioning
confidence: 99%
“…Many researchers report that beginning teachers when transitioning into the profession are optimistic about the challenge before them and provide inclusive learning opportunities (McKay, 2016; McKay et al, 2014; Papatraianou et al, 2018). However, beginning teachers report feeling unsure and unprepared in knowing how to proactively support all students academically and behaviourally (Miles & Knipe, 2018; Serry et al, 2022). Research regarding preservice teachers’ perspectives on inclusion and their preparation and readiness to practice as inclusive educators is extensive (Goddard & Evans, 2018; Hopkins et al, 2018; Mergler et al, 2017; Sharma & Nuttal, 2016; Subban & Mahlo, 2017; Varcoe & Boyle, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Concerns remain about what is taught in the name of inclusive education. These concerns include the adequacy of ITE frameworks for developing pre-service teachers’ skills and strategies (Subban & Mahlo 2017), their preparation to teach and differentiate for diversity (Serry et al, 2022) and their understanding of the DSE standards, particularly students’ rights and their obligations under the standards (de Bruin, 2021). Some research suggests that this preparation can influence whether teachers chose to stay in the profession (Kelly et al, 2019) highlighting the importance of ITE programs to enhance pre-service teachers’ knowledge and understanding of obligation under the DSE to meet the diverse learning and behavioural needs of all students.…”
Section: Introductionmentioning
confidence: 99%